Distributed day‐ahead scheduling in community energy management systems using inter‐community energy trade. Issue 6 (1st February 2018) - Miyamoto, Toshiyuki; Okada, Masahiro; Fukuda, Takuya; Kitamura, Shoichi; Mori, Kazuyuki; Izui, Yoshio
Abstract : A community energy management system (CEMS) stands between energy consumers in a community and energy suppliers, and provides ancillary service to the former. A CEMS performs day‐ahead scheduling for its energy conversion equipment and energy purchase planning for the next day to minimize energy consumption and cost under some constraints. In this study, we assume that multiple CEMSs can cooperatively perform the aforementioned; we examine a day‐ahead scheduling problem among a group of CEMSs using two key solutions for energy saving: demand response and energy trade. Using the demand response, CEMS can change the energy of consumers to improve energy utilization efficiency. Using the energy trade, CEMSs can trade surplus energy with each other. First, we build an optimization problem for a group of CEMSs. Then, the alternating direction method of multipliers is used to decompose the optimization problem into a distributed optimization problem. Results of numerical experiments show that both the demand response and the energy trade cooperatively affect energy saving of the group. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.